The effect of dairy products on the therapeutic regimen of patients with Helicobacter pylori infection in Aden, Yemen - Mohammed, Nashwan Saleh (Journal of medical and pharmaceutical sciences, 2018)
Aim: To determine the effect of intake of dairy products on therapeutic regimen of patients with Helicobacter pylori (H. pylori) infection in Aden, Yemen. Methods: A observational study based on questionnaire and ultrasound imaging. MS Excel was used for data entry and analysis. Ethical concerns done as required including consent forms and acceptance of participants to be involve in the current study. Sample and Sampling: Study sample was consisted of 1300 patients (1000) females and (300) males with confirmed H. pylori history were recruited using a purposeful, non-random sampling. Results: Manifestations and laboratory results revealed 1296 patients with H. Pylori infection treated within two week by triple regime (Amoxicillin 500mg, Clarithromycin 250 mg and Lansoprazole 30 mg every 12 hours daily) with complete prohibition of diary intake, while 4 female patients not strictly stopped consumption of dairy products that failed in eradication of H. pylori infection upon laboratory results. Patients whom not involved in complete restriction of diary intake and given the triple regime get treated after 81 days. Also, patients with Positive H. Pylori Ag in stool samples of the previously treated patients reappeared after re-used of dairy products. In conclusion H. Pylori seriousness represented by its mode of transmission through the food; milk and dairy products. Consumption of dairy products has a negative effect on therapeutic regimen of patients with Helicobacter pylori infection.